Correlated X-ray/UV/optical emission and short-term variability in a Seyfert 1 galaxy NGC 4593. Issue 4 (1st December 2017) - Pal, Main; Naik, Sachindra
Abstract: We present a detailed multifrequency analysis of an intense monitoring programme of Seyfert 1 galaxy NGC 4593 over a duration of nearly for a month with Swift observatory. We used 185 pointings to study the variability in six ultraviolet/optical and two soft (0.3–1.5 keV) and hard X-ray (1.5–10 keV) bands. The amplitude of the observed variability is found to decrease from high energy to low energy (X-ray to optical) bands. Count–count plots of ultraviolet/optical bands with hard X-rays clearly suggest the presence of a mixture of two major components: (i) highly variable component such as hard X-ray emission, and (ii) slowly varying disc-like component. The variations observed in the ultraviolet/optical emission are strongly correlated with the hard X-ray band. Cross-correlation analysis provides the lags for the longer wavelengths compared to the hard X-rays. Such lags clearly suggest that the changes in the ultraviolet/optical bands follow the variations in the hard X-ray band. This implies that the observed variation in longer wavelengths is due to X-ray reprocessing. Though, the measured lag spectrum (lag versus wavelength) is well described by λ 4/3 as expected from the standard disc model, the observed lags are found to be longer than the predicted values from standard disc model. This implies that the actual size of the disc of NGC 4593 is larger than the estimated size of standard thin disc as reported in active galactic nuclei such as NGC 5548 and Fairall 9.